PEMBERDAYAAN SUMBER DAYA MASYARAKAT PESISIR BERBASIS KOPERASI NELAYAN BERKELANJUTAN DI WILAYAH PESISIR SEMARANG - Iin Indarti (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2015)
The general purpose of these paper is to empowerment of fishing society through the strengthening of fisher koperasi as one of the breakthroughs of capital needs to increasing revenue for the break cycle of poor. Model of institutional strengthening directed to revitalized organization and business which has been there. The respondent of these research are people of semarang coast. Primer data was collected in Participatory Rural Appraisal (PRA) method which questionnaire and interview. A data analysis used descriptive analysis. This study identified some of the benefits if fisher join with koperasi are 1. To bulid economies of scale in any transaction in input markets and output markets. So that will achieve efficiency and improved bargaining power to higher prices in the output market and reduce price in input markets. 2. To get external economics that can be encrease productivity.3. To get the benefits of non-economic because of the pooling individuals into groups. So that fishermen decision to join koperasi is a strategic decision and relevant to strengthening the bargaining power in input and output markets and strengthening cooperation in partnership with other external partie.